Environmental concerns in international investment agreements: The 'new era' has commenced, but harmonization remains far off - Kathryn Gordon; Joachim Pohl (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
The authors present findings of a large-sample survey of references to environmental concerns in international investment agreements carried out by the OECD.
Keywords: 330